Insertion companies in social and solidarity economy: perspectives and proposal from FAEDEI - Gil Bartolomé, María Elena; Ramos Rosario, Nieves (Cuadernos de Trabajo Social, 2013)
Main goal of the paper is to introduce new perspectives and proposals put into commission by the Insertion Companies Entrepreneurial Associations Federation (Federación de Asociaciones Empresariales de Empresas de Inserción,FAEDEI) to promote the visibility, development and creation of insertion companies. The paper explains the action frame in which the more than two hundred insertion companies currently operating in Spain develop their social economy model, o model of recognized efficiency for the social and labour insertion of persons with difficulties to access the labour market.